2021
DOI: 10.1155/2021/6577439
|View full text |Cite
|
Sign up to set email alerts
|

Friend-Invitation Promotion Scheme Used in Electric Carsharing: Empirical Analysis and Policy Implications

Abstract: The combination of electric vehicle (EV) and carsharing is expected to provide social and environmental benefits, like encouraging sustainable travel behaviors (reducing car ownership and vehicle kilometres of travel) and improving the accessibility and flexibility of urban transport. Thus, electric carsharing is encouraged to be adopted for daily trips, and the operators propose the friend-invitation promotion scheme for the membership expansion. This study explores the effectiveness of this scheme and the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Cars are owned by a carsharing company, and therefore people do not take ownership responsibilities but pay a small amount of money (compared to the expense of buying a car) for the use of a car, i.e., a large number of users share a small number of vehicles, responsibilities but pay a small amount of money (compared to the expense of buying a car) for the use of a car, i.e., a large number of users share a small number of vehicles, which is regarded as a sustainable solution to increase the usage of vehicles and therefore reduce car ownership, carbon emissions, and the need for land for parking [11][12][13][14][15]. In particular, electric carsharing can further reduce carbon emissions [16,17]. The details of recent research developments in carsharing can be found in the review of Nansubuga and Kowalkowski [18].…”
Section: Introductionmentioning
confidence: 99%
“…Cars are owned by a carsharing company, and therefore people do not take ownership responsibilities but pay a small amount of money (compared to the expense of buying a car) for the use of a car, i.e., a large number of users share a small number of vehicles, responsibilities but pay a small amount of money (compared to the expense of buying a car) for the use of a car, i.e., a large number of users share a small number of vehicles, which is regarded as a sustainable solution to increase the usage of vehicles and therefore reduce car ownership, carbon emissions, and the need for land for parking [11][12][13][14][15]. In particular, electric carsharing can further reduce carbon emissions [16,17]. The details of recent research developments in carsharing can be found in the review of Nansubuga and Kowalkowski [18].…”
Section: Introductionmentioning
confidence: 99%